Reshaping Scholarly Communication Services: Our Path to Open Source - Askey, Dale; Mircea, Gabriela; Perkovic, Olga (My University, 2016)
McMaster Libraries undertook a major project in 2014 to migrate the institutional repository and journal publishing services from a commercially hosted solution (Digital Commons) to in-house supported services based on open source software (DSpace and OJS). This session will focus on the philosophical and financial aspects of this decision as well as the technical and not so technical challenges presented by the project. These include an analysis of risk management with major stakeholders and the creation of a communications plan outlining the transition. While this is not a new technology by any means, it is something of a new tactic to pull something back from a vendor to a campus data centre; things generally run in the opposite direction. We present a case that demonstrates when and where there are advantages to hosting specific services locally to provide optimal service to researchers and to better build and articulate the library’s value.
Keywords: open source software; software migration; open access journals; library services; institutional repository; scholarly communication